Modeling Subsurface Drainage in Compacted Cultivated Histosols - Guedessou, Cedrick Victoir; Caron, Jean; Gallichand, Jacques; Béliveau, Moranne; Dessureault-Rompré, Jacynthe; Libbrecht, Christophe (Frontiers in Water, 2021)
Reclaiming histosols in Montéregie region, Québec, Canada, increases peat decomposition and compaction rate and decreases the effectiveness of subsurface drainage. The objective of this paper was to use HYDRUS-2D to model the behaviour of subsurface drainage systems, in order to evaluate the compaction effect on drain depth and spacing and to determine the compact layer thickness and saturated hydraulic conductivities (Ksat) resulting in an improvement of subsurface drainage. The drainage model was calibrated (NSE = 0.958, PBIAS = -0.57%) using Ksat, meteorological data, and matric potential (h) data measured on the project site from June 10 to July 19, 2017. The calibrated and validated model was used to analyze the variation of h values (△h in cm d-1) as a function of drain spacing (2 to 7m) and drain depth (1m and 1.2m) and to identify the response surface of △h to various compact layer thickness and Ksat combinations. The results showed that △h was on average 58% greater below the compact layer than above it and that reducing drain spacing or increasing drain depth does not improve the drainage rate. The analysis of the compact layer thickness and Ksat effect on △h showed that for a △h of 40 cm d-1, Ksat actual values in the two uppermost layers should be multiplied by 50 for compact layer thickness varying from 12 to 35cm. Water percolation in the soil is reduced by the compact layer. Soil management methods for improving Ksat should therefore be better than deepening the drains or and reducing the spacing.